The Effect of Service Quality and Taste on Customer Satisfaction at Bolu Cukke Hikmah Gattareng Village, Marioriwawo District, Soppeng Regency - Sulfiani, Sulfiani; Asdi, Asdi; Sahib, Muhammad Khaedar (Dinasti Publisher, 2025)
This study aims to analyze the effect of service quality and taste on customer satisfaction at Bolu Cukke Hikmah in Gattareng Village, Soppeng Regency. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data was collected through distributing questionnaires to 100 respondents selected by purposive sampling. The results showed that both service quality and taste have a positive and significant influence on customer satisfaction, both partially and simultaneously. The regression test shows that the service quality variable contributes 70.6% to customer satisfaction, while taste contributes 73.2%. Simultaneously, both variables have a significant effect on customer satisfaction, which indicates that the combination of good service and distinctive taste plays an important role in increasing customer loyalty. Based on these findings, it is recommended that business owners continue to improve service quality and maintain product flavors to maintain customer satisfaction and expand the market.